The Role of School Counselors in Promoting Sanitation Practices and Resilient Communities to Enhance Child Health and Livelihoods - Adaobi Jennifer Iloakasia (Action Research Journal Indonesia (ARJI), 2024)
The study utilized a descriptive survey design to investigate the role of teacher counselors in promoting health and sanitation practices in schools across Anambra State, Nigeria. A purposive sampling technique selected 103 respondents and data were gathered using a structured online questionnaire. The instrument included demographic data, roles, sanitation practices, with responses measured on a 4-point Likert scale. Validated by experts, the questionnaire demonstrated high reliability (Cronbach’s Alpha of 0.65). Data analysis involved calculating frequencies and percentages for each response category. The findings reveal that school counselors significantly contribute to improving sanitation awareness, facilitating community engagement, and implementing effective hygiene programs. A majority of respondents recognized the counselors’ effectiveness in collaborating with local leaders, creating awareness campaigns, and connecting students with sanitation initiatives. The study highlights a strong correlation between counselor-led sanitation programs and improved health outcomes for children, including reduced illness rates and enhanced personal hygiene practices. Furthermore, it emphasizes the necessity for ongoing training and support for counselors to maximize their impact on community resilience and public health.